2020
DOI: 10.3390/math8060969
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Knowledge and Mathematical Intelligence—Two Significant Factors Influencing School Performance

Abstract: Metacognitive knowledge and mathematical intelligence were tested in a group of 280 pupils of grade 7 age 12–13 years in the Czech Republic. Metacognitive knowledge was tested by the tool MAESTRA5-6+. Mathematical intelligence is understood as an important criterion of a learner’s ability to solve mathematical problems and defined as the specific sensitivity to the six particular phenomena: causality, patterns, existence and uniqueness of solution, geometric imagination, functional thinking, and perception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…All the factors influencing the ability to solve mathematical problems can be divided into the three following groups: metacognitive, cognitive, and affective. It has been shown that higher metacognitive knowledge, i.e., the ability to monitor one's activity and regulate learning [45], may increase students' ability to solve mathematical problems [46][47][48][49][50][51][52]. In the affective area, a mutual effect is observed.…”
Section: Mathematical Problem-solvingmentioning
confidence: 99%
“…All the factors influencing the ability to solve mathematical problems can be divided into the three following groups: metacognitive, cognitive, and affective. It has been shown that higher metacognitive knowledge, i.e., the ability to monitor one's activity and regulate learning [45], may increase students' ability to solve mathematical problems [46][47][48][49][50][51][52]. In the affective area, a mutual effect is observed.…”
Section: Mathematical Problem-solvingmentioning
confidence: 99%
“…In this way, affordable mathematical tools provided to students advances learning. Metacognitive knowledge and mathematical intelligence are independent [36]. Metacognitive knowledge can be understood as the ability to recognize the strengths and weaknesses of one's learning process and the subsequent ability to correct them [37], as well as possessing the mathematical intelligence to solve mathematical problems [38].…”
Section: Discussionmentioning
confidence: 99%
“…The first term corresponded to the increase in length due to Hooke's law; the second corresponded to the increase in length due to temperature; the third corresponded to the increase in cable length to be added to the straight line r ab that defined the profile of the cable, s c (see Figures 5 and 6). The negative sign of this third summand corresponded to the fact that point b, when bending the cable in Phase II, moved to the left (negative direction, Equation (36)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations